2019
DOI: 10.1007/s13280-019-01207-9
|View full text |Cite
|
Sign up to set email alerts
|

Bird and invertebrate communities appear unaffected by fracking traffic along rural roads despite dust emissions

Abstract: The development of shale petroleum resources has industrialized rural landscapes. We investigated how traffic from energy development expands and intensifies the road-effect zone through increased dust exposure, and how birds and invertebrates inhabiting the road-effect zone in agricultural areas of the Bakken region might be affected by dust exposure. We used dust collectors, trail cameras, and sweep-netting at increasing distances from unpaved roads to determine dust deposition, relative bird abundance, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 39 publications
(59 reference statements)
0
6
0
Order By: Relevance
“…Several grassland species also did not appear to be physically displaced when exposed to traffic noise at roadside environments (Martinez-Marivela et al, 2018;Daniel & Koper, 2019;Spiess et al, 2020), and traffic noise playbacks in quiet areas (Hawkins et al, 2020;Senzaki et al, 2020). At least one recent study reported that several passerine and non-passerine species were attracted to experimental traffic noise (Hennigar et al, 2019), a finding that contradicted those of previous studies.…”
Section: Impacts On Richness and Abundancementioning
confidence: 93%
See 1 more Smart Citation
“…Several grassland species also did not appear to be physically displaced when exposed to traffic noise at roadside environments (Martinez-Marivela et al, 2018;Daniel & Koper, 2019;Spiess et al, 2020), and traffic noise playbacks in quiet areas (Hawkins et al, 2020;Senzaki et al, 2020). At least one recent study reported that several passerine and non-passerine species were attracted to experimental traffic noise (Hennigar et al, 2019), a finding that contradicted those of previous studies.…”
Section: Impacts On Richness and Abundancementioning
confidence: 93%
“…According to , powerlines, signs and roadside vegetation may provide suitable nesting, refuge, and perching habitats for birds (Spiess et al, 2020). Both Rodgers and Koper (2017), and Nenninger and Koper (2018) observed greater presence of vesper sparrow (Pooecetes gramineus), western meadowlark (Sturnella neglecta), and later savannah sparrow (Passerculus sandwichensis) near natural gas wells and associated roads.…”
Section: Infrastructurementioning
confidence: 98%
“…This might contribute to the fire activity patterns observed in the High Plains, especially, where fire incidence increased substantially after 2008 without a concurrent increase in burned area (Figure 4A). Since the late 2000s, energy development in Colorado has expanded road networks and fragmented wildland landscapes [58,59]; in addition to creating new roads, energy development dramatically increases traffic in rural areas [60]. The industrialization of rural landscapes creates an interface between wildlands and the built environment not currently encompassed in existing definitions of the wildland-urban interface and ought to be explored further in future studies at smaller scales for rural areas where this dynamic might be at play.…”
Section: Human Populationmentioning
confidence: 99%
“…4 Fracking also substantially increases local road traffic, with resulting dust emissions reaching up to 180m into adjacent fields. 13 Focusing on Colorado, Northrup et al 14 document increased avoidance behavior among mule deer around fracking well pads, and Maguire and Papeş1 5 find that grassland bird species diversity declines as the number of shale wells increases. Analyzing grassland bird avoidance behavior around shale oil and gas extraction sites in North Dakota, Thompson et al 16 document avoidance behaviors within 150m of roads and 350m of wells.…”
Section: Introductionmentioning
confidence: 99%
“…Shale oil and gas production creates significant ecosystem disturbances at both drilling and production stages. , These disturbances include air pollution, leakage and leaching of contaminated groundwater, surface spills, light and noise pollution, and generalized increases in human settlement and activity . Fracking also substantially increases local road traffic, with resulting dust emissions reaching up to 180m into adjacent fields . Focusing on Colorado, Northrup et al document increased avoidance behavior among mule deer around fracking well pads, and Maguire and Papeş find that grassland bird species diversity declines as the number of shale wells increases.…”
Section: Introductionmentioning
confidence: 99%